FAKTOR RISIKO KEJADIAN KUSTA DI WILAYAH KERJA PUSKESMAS JUNTINYUAT - Hairil Akbar (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2020)
Background: leprosy transmission is still a public health problem. In several regions in Indonesia the leprosy prevalence rate was still high and the problems caused were complex. Indramayu Regency was classified as a high endemic area of leprosy. This could be seen from the prevalence rate which reached 1.6 per 10,000 population. Data from the Indramayu Regency Health Office showed that in 2017 there were 257 cases of leprosy. Objective: the purpose of this study was to analyze the risk factors for leprosy in the working area of the Juntinyuat Health Center. Methods: this study applied observational analytic study with a case control approach. The number of samples was 60 consisting of 30 cases and 30 controls. The sampling technique was carried out with total sampling that fulfilled the sampling criteria, while the control sample was taken by accidental sampling. The data was processed using the chi-square test. Results: the contact history study (OR = 38.5; CI95%, 7.415-199.8 p = 0.000), occupancy density (OR = 3.50 95% CI, 1.112-11.017 p = 0.028), and personal hygiene (OR = 3.14; 95% CI, 1.066-9.267 p = 0.035). Conclusion:  Therefore, in can be concluded that contact history, occupancy density, and personal hygiene were risk factors for leprosy in the working area of Juntinyuat Health Center.